2013
DOI: 10.2308/ajpt-50533
|View full text |Cite
|
Sign up to set email alerts
|

Auditor Choice and Audit Fees in Family Firms: Evidence from the S&P 1500

Abstract: SUMMARY We examine auditor choice and audit fees in family firms using data from Standard & Poor's (S&P) 1500 firms. We find that, compared to non-family firms, family firms are less likely to hire top-tier auditors due to the less severe agency problems between owners and managers. Our results also show that family firms, on average, incur lower audit fees than non-family firms, which is driven by family firms' lower demand for external auditing services and auditors' perceived lower au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
178
4
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(216 citation statements)
references
References 42 publications
21
178
4
3
Order By: Relevance
“…However, the demand for Big 4 auditors increases when the controlling shareholder is not a family member. Ho and Kang () found evidence consistent with this premise for a sample of US firms. Chen, Cheng, and Dai () argued that the selection of an auditor depends on the person or individuals who run the business, because the founder, descendants, and professional CEOs vary with respect to their sense of identity, psychological attachment to the firm, and management incentive mechanisms.…”
Section: Determinants Of Auditor Choicementioning
confidence: 68%
“…However, the demand for Big 4 auditors increases when the controlling shareholder is not a family member. Ho and Kang () found evidence consistent with this premise for a sample of US firms. Chen, Cheng, and Dai () argued that the selection of an auditor depends on the person or individuals who run the business, because the founder, descendants, and professional CEOs vary with respect to their sense of identity, psychological attachment to the firm, and management incentive mechanisms.…”
Section: Determinants Of Auditor Choicementioning
confidence: 68%
“…Simunic's audit fee model () suggests that the audit fee is influenced by audit effort. The literature suggests that auditors increase audit efforts in firms that are assessed to have higher business risk (Bell et al, ; Srinidhi et al, ), higher risk of material misstatement (Ghosh & Tang, ), lower earnings quality (Fan & Wong, ), higher risk of accounting fraud (Kim et al, ), and poor firm governance (Bedard & Johnstone, ; Ho & Kang, ). Since evidence suggests that the entrenchment effect is more dominant in Malaysian family firms, auditors assign them higher risks of fraudulent reporting or financial misstatement.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…At a glance, results from Table suggest that auditor choice may have explained why CEO power is associated with lower audit fees. However, the supply side theory (Simunic, ) argues and shows that audit risk is lower in firms with higher accruals quality (Kim et al, ; Srinidhi et al, ), strong firm governance (Bedard & Johnstone, ; Srinidhi et al, ), higher financial performance (Bell et al, ; Ho & Kang, ), and lower financial leverage (Ghosh & Tang, ). As hypothesized, this study argues that CEO power can indirectly influence audit fees via accruals quality, firm governance, financial performance, and financial leverage.…”
Section: Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that monitoring by higher‐quality auditors can reduce insiders' incentives and ability to render financial statements less informative, thereby alleviating the problem of agency conflict between insiders and outsiders by mitigating information asymmetry (e.g., Becker, DeFond, & Jiambalvo, ). However, to date, few studies have examined auditing issues in family firms (Ho & Kang, ; Trotman & Trotman, ). This study adds to the existing literature by investigating whether family ownership and control configurations are systematically associated with a firm's choice of auditor.…”
Section: Introductionmentioning
confidence: 99%